Body Composition in Patients with Stable Chronic Obstructive Pulmonary Disease: Comparison with Malnutrition in Healthy Smokers - Baccioglu, Ayse (Eurasian J Med, 2014)
OBJECTIVE: Although malnutrition (body mass index (BMI)<18.5kg/ m(2)) has been associated with impaired health status in patients with chronic obstructive pulmonary disease (COPD), the effects of body composition (body fat and protein percentage) in patients with COPD have not been clearly demonstrated. MATERIALS AND METHODS: A total of 180 stable patients with COPD at the stages of moderate, severe, very severe, and 50 healthy subjects were included in this prospective study. All subjects underwent a clinical evaluation, spirometry tests, anthropometric measurements and blood analysis. RESULTS: Frequency of underweight was higher in COPD (11.7%) patients than the control group (8%). The frequency of underweight increased as the severity of COPD worsens. There was body decomposition (protein or fat depletion) in not only all underweight patients but also some normal/overweight COPD patients, as well as in the healthy subjects. Deterioration in FEV(1) (L), and FEV(1)/FVC was more evident in underweight patients with protein and fat depletion compared to normal/overweight patients (p=0.004, and p=0.005). Inspiratory and expiratory respiratory muscle power was lower in under-weight patients with depletion than in normal/overweight patients (p=0.02, and p=0.01). DLCO and DLCO/VA were significantly lower in underweight patients than in normal/overweight patients (p=0.003, and p=0.004), they were also lower in normal/overweight patients with depletion than in normal/overweight patients with no depletion (p=0.01, and p=0.07). Normal/overweight patients with protein depletion had the most frequent number of exacerbations than others (p=0.04). CONCLUSION: These results show that the body decomposition is important in patients with COPD. Assessment of body composition should be a part of nutritional assessment besides BMI in patients with COPD.